Association between Healthcare Providers’ Knowledge and Adherence to Ventilator-Associated Pneumonia Prevention Guidelines - Jan, Mahmood; Muzammil, Hafiz Shehzad; Rashid, Sana; Faruqi, Amdad (Indus Journal of Bioscience Research, 2025)
Ventilator-associated pneumonia (VAP) represents a prevalent and serious healthcare-associated infection among mechanically ventilated ICU patients. While evidence-based preventive measures can substantially reduce VAP incidence, their effectiveness depends on healthcare providers' (HCPs) knowledge and compliance. This study evaluated the relationship between HCPs' knowledge and adherence to VAP prevention guidelines in ICUs of public sector tertiary care hospitals in Peshawar, Pakistan. A cross-sectional study was conducted with 140 healthcare professionals (HCPs), including nurses, respiratory therapists, and physicians, using convenience sampling. Data were collected through a structured questionnaire assessing demographics, knowledge, and self-reported practices, analyzed via SPSS v25 using descriptive and inferential statistics (chi-square, ANOVA). Participants were predominantly male (60%), respiratory therapists (46.4%), with 79.3% having 1 month to 5 years ICU experience. While 73.6% reported formal VAP training, significant knowledge-practice gaps emerged: 92.9% knew the correct head-of-bed elevation (30-45°), but only 78.6% consistently practiced it; 70.7% recognized ideal oral care frequency ("every shift"), yet 57.1% performed it twice daily. Although 75% identified chlorhexidine as the preferred antiseptic, application remained inconsistent. Significant profession-based variations were observed. Chi-square tests revealed associations between professional role and oral care frequency (p=0.040) and antiseptic selection (p=0.041). ANOVA showed differences in early mobility understanding across professions (p=0.027). Despite adequate knowledge, adherence to critical practices (sedation interruption, subglottic suctioning) varied substantially by role. The study demonstrates persistent gaps between VAP prevention knowledge and practice, influenced by professional background, training inconsistencies, and systemic factors. Findings underscore the need for role-specific training, clinical audits, and strengthened institutional protocols to bridge these gaps. A multidisciplinary approach combining education, monitoring, and system-level support is essential to reduce VAP incidence and promote evidence-based critical care.